Rethinking time, culture and socioeconomic organisation in Bronze Age Transylvania. (February 2020) - Quinn, Colin P.; Ciugudean, Horia; Bălan, Gabriel; Hodgins, Gregory
Abstract: Abstract : South-west Transylvania was an important source of metal and other natural resources for Bronze Age Europe, helping to facilitate the development of increasingly hierarchical societies. The absence of a radiocarbon-based chronology for Transylvania, however, has impeded understanding of the region's role within broader socioeconomic networks. Here, the presentation of the first radiocarbon chronology for the Wietenberg Culture in south-west Transylvania allows the authors to highlight the importance of interregional exchange and reliable access to metal for Bronze Age European societies, and emphasise that resource-procurement zones follow unique trajectories of socioeconomic organisation.